Rational approach to the prescription of anti-rheumatic drugs in rheumatoid arthritis: a product leaflet-based strategy in Italy - Perricone, Carlo; Castellucci, Andrea; Cafaro, Giacomo; Calvacchi, Santina; Bruno, Lorenza; Dal Pozzolo, Roberto; Tromby, Francesco; Colangelo, Anna; Gerli, Roberto; Bartoloni, Elena (Frontiers in Immunology, 2024)
The treatment of patients with rheumatoid arthritis (RA) has dramatically changed in the past 30 years. Currently, numerous conventional, biologic, and targeted synthetic DMARDs have been licensed and used following recommendations provided by international and national scientific societies. However, the availability of biosimilars and the increasing necessity of savings impacted on the local/national prescription of these drugs. The information provided by data sheet of every single drug is a decisive factor on the choice of a certain treatment merged with the patient's profile. Thus, our purpose was to construct a rational algorithm for the treatment strategy in RA according to costs and the product leaflet of the biologic and targeted-synthetic DMARDs currently licensed in Italy. We used the most recent available recommendations and then we performed a review of the literature considering all the factors that are known to influence drug safety/effectiveness. All these factors were considered in the context of the data sheets of currently available originators and biosimilars.